Sedation in Pediatric Esophagogastroduodenoscopy - Seak Hee Oh (Korean Society of Gastrointestinal Endoscopy, 2018)
Pediatric esophagogastroduodenoscopy (EGD) has become an established diagnostic and therapeutic modality in pediatric gastroenterology. Effective sedation strategies have been adopted to improve patient tolerance during pediatric EGD. For children, safety is a fundamental consideration during this procedure as they are at a higher risk of severe adverse events from procedural sedation compared to adults. Therefore, a detailed risk evaluation is required prior to the procedure, and practitioners should be aware of the benefits and risks associated with sedation regimens during pediatric EGD. In addition, pediatric advanced life support by endoscopists or immediate intervention by anesthesiologists should be available in the event that severe adverse events occur during pediatric EGD.